Keanekaragaman Jenis Lichen di Kota Semarang - Mafaza, Husna; Murningsih, Murningsih; Jumari, Jumari (Universitas Negeri Semarang, 2019)
Lichen is often used as a bioindicator of air pollution in an area because it is sensitive to pollution. The morphological structure of lichen that does not have a cuticle, stomata, and absorptive organ, forces lichens to survive under the stress of pollutants found in the air. The sensitivity of lichen to air pollution can be seen through changes in diversity. The purpose of this study was to examine the diversity of species of lichens, to assess the environmental conditions and shade trees as habitat for lichens in the city of Semarang. The research was conducted from October to November 2017 using the purposive random sampling method. Sampling was conducted at three research stations, namely: Mangkang Terminal, Simpang Lima Area, and Undalang Tembalang Campus. Based on the results of research at the three observation stations, 18 lichen species were obtained, 13 species were identified and 5 species were not identified. Lichen obtained as many as 8 families, namely Arthoniaceae, Caloplacaceae, Physciaceae, Graphidaceae, Lecanoraceae, Lecidellaceae, Leprariaceae and Parmeliaceae. These types of lichen belong to the talus group foliose and crustose. The shade tree that is most overgrown with lichens is mahogany (Swietenia mahagoni). The Shannon-Wiener diversity index values in the three research stations were: Terminal Mangkang (1.88), Simpang Lima Region (2.95), and Undip Tembalang Campus (3.71). The highest number of species and number of individuals is at the Undip Tembalang Campus, with a total of 17 species and 295 individuals lichen. Dirinaria spp. is the most found species in all three research stations. Lichen sering dipakai sebagai bioindikator pencemaran udara di suatu daerah karena sifatnya yang sensitif terhadap polusi. Struktur morfologi lichen yang tidak memiliki lapisan kutikula, stomata, dan organ absorptif, memaksa lichen untuk bertahan hidup di bawah cekaman polutan yang terdapat di udara. Sensitivitas lichen terhadap pencemaran udara dapat dilihat melalui perubahan keanekaragamannya. Tujuan dari penelitian ini adalah untuk mengkaji keanekaragaman jenis lichen, mengkaji kondisi lingkungan dan pohon peneduh sebagai habitat lichen di Kota Semarang. Penelitian dilaksanakan pada bulan Oktober hingga November 2017 menggunakan metode purposive random sampling. Sampling dilakukan di tiga stasiun penelitian, yakni: Terminal Mangkang, Kawasan Simpang Lima, dan Kampus Undip Tembalang. Berdasarkan hasil penelitian di ketiga stasiun pengamatan, diperoleh 18 spesies lichen, 13 spesies berhasil diidentifikasi dan 5 spesies belum teridentifikasi. Lichen yang diperoleh sebanyak 8 famili yakni Arthoniaceae, Caloplacaceae, Physciaceae, Graphidaceae, Lecanoraceae, Lecidellaceae, Leprariaceae dan Parmeliaceae. Jenis lichen tersebut termasuk dalam kelompok talus foliose dan crustose. Pohon peneduh yang paling banyak ditumbuhi lichen adalah mahoni (Swietenia mahagoni). Nilai indeks keanekaragaman Shannon-Wiener di ketiga stasiun penelitian yaitu: Terminal Mangkang (1,88), Kawasan Simpang Lima (2,95), dan Kampus Undip Tembalang (3,71). Jumlah jenis dan jumlah individu tertinggi terdapat di Kampus Undip Tembalang, dengan total 17 spesies dan 295 individu lichen. Dirinaria spp. merupakan spesies yang paling banyak ditemukan di ketiga stasiun penelitian.